2021
DOI: 10.3892/mco.2021.2473
|View full text |Cite
|
Sign up to set email alerts
|

Study of microRNA expression profiling as biomarkers for colorectal cancer patients in Lebanon

Abstract: The high incidence and mortality rates of colorectal cancer (CRC) reveal its hazardous effect globally. Thus, it is important to diagnose CRC at an early stage to decrease its burden and improve survival rates. Previous studies have investigated the role of short non-coding microRNAs (miRNAs or miRs) in numerous types of cancer, including CRC. Previous studies have been performed to investigate the role of miRNAs as biomarkers in diagnosis, prognosis and prediction of CRC development. The aim of the present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 52 publications
(61 reference statements)
0
2
0
1
Order By: Relevance
“…On the other hand, miR-21 has oncogenic functions, as its levels are elevated in CC tissue compared to normal tissue, especially in early stages [30]. Similarly, miR-31 and miR-146b are oncogenic biomarkers for CC [31].…”
Section: Diagnostic and Screening Biomarkersmentioning
confidence: 99%
“…On the other hand, miR-21 has oncogenic functions, as its levels are elevated in CC tissue compared to normal tissue, especially in early stages [30]. Similarly, miR-31 and miR-146b are oncogenic biomarkers for CC [31].…”
Section: Diagnostic and Screening Biomarkersmentioning
confidence: 99%
“…Sin embargo, ninguno ha demostrado ser del todo eficiente, por lo que en los últimos años se ha realizado la búsqueda de nuevas moléculas que puedan ser empleadas como marcadores para la detección oportuna de enfermedades renales incluida la ND. En este sentido, los micro RNAs (miRNAs), así como sus genes blancos han llamado la atención como potenciales moléculas específicas para la detección y monitoreo de distintas enfermedades metabólicas y de distintos tipos de cáncer (3). Los miRNAs son transcritos de cadena corta (∼22 nucleótidos), no codificantes, que regulan de manera post-transcripcional la expresión de genes blancos y sus proteínas derivadas, a través de la degradación del mRNA o represión de la traducción (4,5).…”
Section: Introductionunclassified
“…For example, a study found that a panel of miRNAs (e.g., miR-21, miR-31, miR-146a, and miR-192) had a sensitivity and a specificity for detecting CRC [23]. Even though these studies demonstrate the potential of miRNA as a non-invasive biomarker for CRC, more research is still needed to validate these findings in larger patient populations [24][25][26]. The type of cancer and stage of the disease can impact the miRNA signature.…”
Section: Introductionmentioning
confidence: 99%